Dalihan Na Tolu: A Cultural Framework for Religious and Social Harmony in Padangsidimpuan - Mukti Ali (Sufiya Journal of Islamic Studies, 2024)
This research aims to examine the role of Dalihan Na Tolu values in creating harmonious social-religious relations in Neighborhood I of Losung Village, Padangsidimpuan. Dalihan Na Tolu, as the kinship system of the Angkola Batak community, is believed to be not only a guideline in the family structure, but also affects the pattern of social interaction involving various religious backgrounds. This research uses a qualitative approach with a case study method, where data is obtained through in-depth interviews, observation, and documentation. The results showed that Dalihan Na Tolu values are actualized in people's daily lives through mutual respect, help, and maintaining the boundaries of each other's beliefs, both in social interactions, religious events, and death moments. This finding indicates that local wisdom plays a strategic role in building a harmonious and tolerant society culturally and religiously. Thus, Dalihan Na Tolu can be understood as an effective form of cultural articulation in maintaining religious social harmony in the midst of diversity.